The Effect of Flash Sale And Free Shipping on Impulsive Buying through Positive Emotions as Intervening Variables (Case Study of Shopee Application Users in Surabaya Area) - Savira Maslihatul Mamlu'ah; Sonja Andarini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to determine and analyze the effect of flash sales and free shipping on impulsive purchases through positive emotions as an intervening variable among Shopee application users in the Surabaya area. This research uses quantitative research, with the research method used being a questionnaire distributed online using non-probability sampling. The results of this research on the first hypothesis (flash sales on positive emotional variables) and the sixth hypothesis (flash sales on impulsive purchases through positive emotions) have no effect, while the results from the second to seventh hypotheses have an effect. Flash sales and free shipping can be more effective tools in enhancing the shopping experience, ultimately contributing to consumers' impulsive purchasing behavior. This research also shows that marketing strategies that rely solely on flash sales should be considered carefully, because although effective in triggering impulse purchases, they do not always create a strong emotional impact on consumers.